Quantitative wood anatomy and stable carbon isotopes indicate pronounced drought exposure of Scots pine when growing at the forest edge - Buras, Allan; Rehschuh, Romy; Fonti, Marina; Lange, Jelena; Fonti, Patrick; Menzel, Annette; Gessler, Arthur; Rigling, Andreas; Treydte, Kerstin; von Arx, Georg (Frontiers in Forests and Global Change, 2023)
Climate change poses a major threat to global forest ecosystems. In particular, rising temperatures and prolonged drought spells have led to increased rates of forest decline and dieback in recent decades. Under this framework, forest edges are particularly prone to drought-induced decline since they are characterized by warmer and drier micro-climatic conditions amplifying impacts of drought on tree growth and survival. Previous research indicated that forest-edge Scots pine trees have a higher growth sensitivity to water availability compared to the forest interior with consequent reduction of canopy greenness (remotely sensed NDVI) and higher mortality rates. Yet, the underlying physiological mechanisms remain largely unknown. Here, we address this knowledge gap by comparing stable carbon isotope signatures and wood anatomical traits in annual rings of trees growing at the forest edge vs. the forest interior and between trees that either survived or died during the extreme drought of 2015. Our analyses suggest that the exposure to drought of forest-edge Scots pine likely results in a reduction of stomatal conductance, as reflected by a higher δ 13 C of stem wood, thinner cell-walls, and lower mean ring density. Moreover, we found dead trees to feature larger mean hydraulic lumen diameters and a lower cell-wall reinforcement, indicating a higher risk to suffer from cavitation and embolism. In conclusion, the typically drier micro-climatic conditions at the forest edge seem to have triggered a larger reduction of stomatal conductance of Scots pine trees, resulting in a lower carbon availability and significantly altered wood anatomical properties under an increasingly drier climate.